Relationship Between Different Types and Forms of Anti-Asthmatic Medications and Dental Caries in Three to 12 Year Olds - Alireza Heidari; Bahman Seraj; Mahdi Shahrabi; Hamideh Maghsoodi; Mohammad Javad Kharazi Fard; Tara Zarabian (Tehran University of Medical Sciences, 2016)
Objectives: Asthma is a common chronic disease. Asthma and anti-asthmatic medications have been suggested as risk factors for increased susceptibility to caries. This study was conducted to evaluate the effects of different types and forms of antihistaminic medications and the duration of drug consumption on the severity of dental caries in asthmatic children. Materials and Methods: This cross-sectional study was conducted in Asthma and Allergy Department of Children's Medical Center in Tehran, Iran. Eighty-five children between three to 12 years who had been diagnosed with asthma, by means of taking medical history, clinical examination and spirometry were chosen by non-simple random sampling. The participants and their parents were interviewed. Oral examination was performed by a qualified dentist. The data were collected by use of questionnaires and analyzed by the stepwise multivariate linear regression analysis, using SPSS version 16. P<0.05 was considered statistically significant. Results: There was a significant correlation between the number of cetirizine and ketotifen tablets taken and decayed/missing/filled (dmf/DMF) teeth score (P=0.006). There were no correlations between the number of consumed sprays and dmf/DMF score (P=0.923), the duration of drug therapy (P=0.907) or the type of medication taken including ß2 agonists, antihistamines, steroids or a combination of them (P=0.907). Conclusions: The present study showed that the tablet form of medications significantly increased the severity of dental caries even in presence of confounders (sex, age, duration of disease, tooth brushing, sugar consumption, fluoride therapy, mouth dryness).